2017
DOI: 10.3389/fpsyg.2017.01915
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence That the Effects of Repetition on Subjective Time Depend on Repetition Probability

Abstract: Repeated stimuli typically have shorter apparent duration than novel stimuli. Most explanations for this effect have attributed it to the repeated stimuli being more expected or predictable than the novel items, but an emerging body of work suggests that repetition and expectation exert distinct effects on time perception. The present experiment replicated a recent study in which the probability of repetition was varied between blocks of trials. As in the previous work, the repetition effect was smaller when r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“… Matthews’ (2015) suggests that repetition of stimuli exerts opposing effects on perceived duration: a first-order repetition effect, related to a low-level adaptation process, reduces perceived duration, while a higher-order repetition effect, which is associated with expectations about repetition, increases perceived duration. Skylark and Gheorghiu (2017) replicated Matthews’ (2015) study, reporting the same pattern of results using slightly different stimuli and different durations for the first and second stimuli.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“… Matthews’ (2015) suggests that repetition of stimuli exerts opposing effects on perceived duration: a first-order repetition effect, related to a low-level adaptation process, reduces perceived duration, while a higher-order repetition effect, which is associated with expectations about repetition, increases perceived duration. Skylark and Gheorghiu (2017) replicated Matthews’ (2015) study, reporting the same pattern of results using slightly different stimuli and different durations for the first and second stimuli.…”
Section: Introductionsupporting
confidence: 57%
“…The fact that perceived duration is affected by the observer’s expectations about stimuli is of particular interest here; how this phenomenon operates is still an open question. There is existing evidence to suggest that fulfilled expectations reduce ( Tse et al, 2004 ; Ulrich et al, 2006 ; Pariyadath and Eagleman, 2007 , 2012 ; Matthews, 2011 ; Schindel et al, 2011 ), do not reduce ( van Wassenhove et al, 2008 ; Cai et al, 2015 ), or even increase perceived duration of a stimulus ( Matthews’, 2015 ; Matthews and Gheorghiu, 2016 ; Matthews and Meck, 2016 ; Schweitzer et al, 2017 ; Skylark and Gheorghiu, 2017 ; Birngruber et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By modulating the predictability of stimulus sequences, Cai et al (2015) found results suggesting that repetitions alone, and not expectations, might be the driving force behind the oddball effect. However, follow-up work demonstrated that the rate of stimulus repetition (Matthews, 2015;Skylark & Gheorghiu, 2017), and the expected sequential position of an oddball both modulate their effect on subjective duration (Wehrman et al, 2018). In addition, it has been shown that the degree to which the oddball physically differs from the standards can scale the temporal oddball effect (Kim & McAuley, 2013;Schindel et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the number of changes (e.g., varying the angles of lines) between the oddball and standard stimuli has been shown to modulate the magnitude of the oddball effect (Schindel et al, 2011;Pariyadath and Eagleman, 2012). However, more recent studies found that the repetition duration compression was reduced or even reversed when repeats were frequent compared with when repeats were rare across blocks, indicating an interaction between low-sensory adaptation and high-level expectation (Matthews, 2015;Skylark and Gheorghiu, 2017).…”
Section: Introductionmentioning
confidence: 99%